Mixed-Valent Selenium Ligands in the Uncharged Iridium Complexes [Ir4Se10Br16] and [Ir6Se8Cl30] - Stolze, Karoline; Rasche, Bertold; Ruck, Michael (European Journal of Inorganic Chemistry, 2015)
The reaction of Ir with Se and SeBr4 at 200 °C yields shiny vermillion slate-like crystals of the new compound Ir4Se10Br16. Single-crystal X-ray diffraction revealed an orthorhombic unit cell, space group Pccn, with lattice parameters a = 1515.0(1) pm, b = 1534.4(1) pm, and c = 1514.5(1) pm at 296(1) K. The crystal structure consists of uncharged tetranuclear iridium complexes [Ir4Se10Br16] with C2 symmetry. In the [(Ir3+)4(μ4-η2-Se22-)2(μ-ηSe-[SeBr]-)2(ηSe-SeBr2)4(μ-Br-)2(Br-)4] complex, each of the iridium atoms is coordinated octahedrally by four selenium and two bromine atoms. Selenium adopts three different oxidation states: -I in the fourfold-bonded diselenide dumbbell, ±0 in the bridging [SeBr]- unit, and +II in the terminal SeBr2 ligand. An analogous reaction with SeCl4 at 300 °C yields orange air-stable crystals of Ir6Se8Cl30. The triclinic crystal structure [space group P1, a = 891.2(1) pm, b = 1064.6(1) pm, c = 1263.0(1) pm, α = 94.458(3)°, β = 106.900(3)°, and γ = 101.410(3)° at 296(1) K] consists of uncharged hexanuclear iridium complexes with the structured formula [(Ir3+)6(μ-ηSe-[SeCl]-)2(ηSe-SeCl2)6(μ-Cl-)10(Cl-)6] and shows structural motifs similar to Ir4Se10Br16 and IrSeCl5. The triclinic structure of IrSeCl5 [P1, a = 1223.4(1) pm, b = 1408.7(1) pm, c = 1499.5(1) pm, α = 115.72(1)°, β = 106.05(1)°, and γ = 96.38(1)° at 296(1) K] is homeotypic to monoclinic RhSCl5.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Coordination compounds; Diselenides; Iridium; Mixed-valent compounds; Ring-shaped complexes